A Validated Method for the Quantitation of Ciprofloxacin Hydrochloride Using Diffuse Reflectance Infrared Fourier Transform Spectroscopy. (5th February 2014) - Bhongade, Bhoomendra; Talath, Sirajunisa; Dhaneshwar, Sunil
Abstract : A quantitative method using diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) was developed and validated for the estimation of ciprofloxacin in its tablet dosage forms. The solid-state samples were prepared by dilution in dry potassium bromide and were analyzed by FTIR spectrophotometer with DRIFT sampling technique. A linear relationship for the carbonyl peak area centered around 1709 cm −1 was observed in the range of 0.3–1.5% w/w with good correlation coefficient of 0.998. The percent recovery of ciprofloxacin in three marketed tablet dosage forms was in the range of 98.76 ± 0.27. The present reported method is precise, reproducible, and eco-friendly. DRIFTS may have a potential as an alternative method for qualitative and quantitative analysis of ciprofloxacin in bulk drugs and tablet dosage forms.